Utilization of Coffee Pod Waste as an Alternative Planting Medium for Anthurium (Anthurium plowmanii Scoat.) - Roni Wibowo (Contributions of Central Research Institute for Agriculture, 2021)
This research was conducted with the aim of getting the composition alternative growing media for Anthurium plowmanii Scoat. By utilizing the waste coffee fruit skin. The hypothesis proposed is that the composition of various planting media using coffee pod waste provides various growth responses for Anthurium plants. Anthurium (Anthurium sp.) is one type of ornamental leaf plant that needs attention to be developed in Indonesia. Fern chopped planting medium has the characteristics of easily binding water, having good aeration and drainage. Meanwhile, bamboo leaf humus media has the characteristics of easily binding and retaining water, contains high levels of nutrients, and has a high cation exchange capacity. Therefore, it is expected that the composition of this planting medium can maintain moisture, fertile, It is porous and has good aeration so it can support the growth of Anthurium plants. However, if the use of this type of planting media is often used, especially chopped ferns, then one day its availability in nature will decrease and it will likely be difficult to obtain. Therefore, efforts are needed to find new alternative media that can provide good growth for Anthurium plants in addition to chopped fern and bamboo leaf humus. The alternative planting media used can come from materials from agricultural waste either in the form of crop residues or crop residues which are widely available and thrown away without any utilization. One of the crop residues that has the potential to be used as a planting medium is coffee pod skin waste. Coffee pod waste contains high levels of Nitrogen and Potassium nutrients. In addition to containing nutrients, coffee pod waste also contains tannin compounds. These compounds can inhibit the growth and development of plants so that when using the coffee berry skin media, a soaking or washing process must be carried out so that it can be used.